Answer:get what
Step-by-step explanation:
<span>D) perpendicular bisector <em>I believe.
</em></span>
A:
(f+g)(x)=f(x)+g(x)
(f+g)(x)=4x-5+3x+9
(f+g)(x)=7x+4
B:
(f•g)(x)=f(x)•g(x)
(f•g)(x)=(4x-5)(3x+9)
(f•g)(x)=12x^2-15x+36x-45
(f•g)(x)=12x^2+21x-45
C:
(f○g)(x)=f(g(x))
(f○g)(x)=4(3x+9)-5
(f○g)(x)=12x+36-5
(f○g)(x)=12x+31
Answer:
12
Step-by-step explanation:
3x^2
because the information provided states that x = -2, that is what we are going to replace x with.
3(-2)^2
the next step is to evaluate the power because that is next in PEMDAS.
(-2)^2 = 4
that leaves us with:
3 * 4 = 12 ( the " * " represents the multiplication sign)
hope this helps!